Chemical competence of future pharmacists - Brytanova, T. S.; Hotsulia, A. S.; Британова, Тетяна Сергіївна; Гоцуля, Андрій Сергійович (Запорізький державний медичний університет, 2023)
The formation of the necessary conditions for the development and self-realization of each individual remains the main goal of the educational system of Ukraine. And this in wartime conditions. But the Ukrainian nation is strong and indomitable. Ready to work efficiently and persistently even under such conditions. Ready to educate new generations of specialists for the future prosperity of our country. The implementation of a competent approach in the field of higher education involves the training of a competitive specialist in accordance with global trends, which ensures his effective professional activity. Such a specialist is able to actively adapt to the changing conditions of his functioning and always requires constant self-development [2].